Selection criteria in organic cattle breeding - Savić Mila; Dimitrijević Vladimir; Trailović Ružica; Vegara Mensur; Dimitrijević Blagoje; Bečkei Žolt; Petrujkić Branislav; Cojkić Aleksandar (Veterinarski Glasnik, 2014)
The central issue in process of organizing organic cattle breeding is the knowledge about specificities of this kind of production, good knowledge of breed characteristics (body composition, immune tolerance, expressed predisposition towards some diseases, production properties). Research centres, in collaboration with producers, have defined the essential features on which the selection programmes in organic cattle breeding are based on. Of the greatest importance for veterinary service is the fact that selection programmes in organic cattle breeding are in the first place based on giving priority to healthy animals, with strong immune system, good reproductive characteristics, which can be in production system for a long period. Additional important selective criteria is specific body resistance and adaptability of autochtonous breeds to environmental conditions. [Projekat Ministarstva nauke Republike Srbije, br. TP 31085]